Getting the Right Evidence After Drug Approval - Vreman, Rick A.; Leufkens, Hubert G. M.; Kesselheim, Aaron S. (Frontiers in Pharmacology, 2020)
To generate comparative evidence in a timely fashion for drugs without restricting or delaying access, value-based pricing and reimbursement could be conditioned on a prospective, post-approval evidence generation plan.